UPAYA PENINGKATAN AKTIFITAS DAN PRESTASI BELAJAR BIOLOGI SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI SMPN 5 KOTA BENGKULU - JULIARTI JULIARTI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to increase student activity and achievement in class VIII biology at SMP Negeri 5 Bengkulu City for the 2021/2022 academic year. This type of research is classroom action research (PTK) which has been carried out in three cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects in this study were class VIIIB students at SMP Negeri 5 Bengkulu City for the 2021/2022 academic year. The objects in this research are student activities, teacher activities and student achievement. Data collection techniques in this study are in the form of tests and non-tests (observation). Data analysis used descriptive analysis techniques. The data obtained in this study were implementation data of lesson plans (teacher activities), student activity data and learning achievement tests. Based on the research results, it was obtained that the percentage of implementation of lesson plans in cycles I, II and III was 100%, including the category "very appropriate to lesson plans". Student activity data in cycle I obtained a score of 20 (active), in cycle II obtained a score of 25 (very active), and in cycle III obtained a score of 26 (very active). While the student achievement data in cycle I obtained an average of 49.31 with a percentage of learning completeness of 10.34%, in cycle II obtained an average of 63.21 with a percentage of learning completeness of 50%, in cycle III obtained an average -an average of 86.67 with a learning completeness percentage of 96.67%. Based on the results of this study, it can be concluded that the Jigsaw cooperative learning model can increase student learning activities and achievements at SMP Negeri 5 Bengkulu City in the 2021/2022 academic year. ABSTRAKPenelitian ini bertujuan untuk meningkatkan aktivitas dan prestasi belajar siswa pada mata pelajaran biologi kelas VIII di SMP Negeri 5 Kota Bengkulu tahun ajaran 2021/2022. Jenis penelitian ini adalah penelitian tindakan kelas (PTK) yang telah dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, pengamatan dan refleksi. Subyek dalam penelitian ini adalah siswa kelas VIIIB di SMP Negeri 5 Kota Bengkulu tahun ajaran 2021/2022. Obyek dalam penelitian ini adalah aktivitas siswa, aktivitas guru dan prestasi belajar siswa. Teknik pengumpulan data dalam penelitian ini yaitu berupa tes dan non tes (observasi). Analisis data menggunakan teknik analisis deskriptif. Data yang diperoleh pada penelitian ini yaitu data keterlaksanaan RPP (aktivitas guru), data aktivitas siswa serta tes prestasi belajar. Berdasarkan hasil penelitian, diperoleh persentase keterlaksanaan RPP pada siklus I, II dan III sebesar 100% termasuk kategori “sangat sesuai RPP”. Data aktivitas siswa pada siklus I diperoleh skor 20 (aktif), pada siklus II diperoleh skor 25 (sangat aktif), dan pada siklus III diperoleh skor 26 (sangat aktif). Sedangkan data prestasi belajar siswa pada siklus I diperoleh rata-rata sebesar 49,31 dengan persentase ketuntasan belajar sebesar 10,34%, pada siklus II diperoleh rata-rata sebesar 63,21 dengan persentase ketuntasan belajar sebesar 50%, pada siklus III diperoleh rata-rata sebesar 86,67 dengan persentase ketuntasan belajar sebesar 96,67%. Berdasarkan hasil penelitian tersebut, maka dapat disimpulkan bahwa model pembelajaran kooperatif tipe Jigsaw dapat meningkatkan aktivitas dan prestasi belajar siswa di SMP Negeri 5 Kota Bengkulu tahun ajaran 2021/2022.